(untitled) (Physical Education, Health and Social Sciences, 2025)
The objectives of the study were to investigate students’ attitude towards science and its relationship with academic achievements. Survey research design was used for data collection. Moreover, a comparative design was also used to compare variables on gender basis. Population of the study were all the secondary level students studying in 9th and 10th classes in public sector schools at lower Dir where 32471 science students were enrolled. The population was scattered so 320 samples (240 males and 80 Female) were selected as sample. Simple random sampling method was used for data collection. An already developed standardized scale TOSRA (1981) (Test of science-related attitude) was used and modified. The validity of the instrument was found qualitatively by two subject experts in our own culture and no ambiguity and difficulty was determined in understanding of the items in this scale. Two factors attitude of science inquiry having reliability value .78 and career interest in science having reliability value .81 were selected for the final scale. To find the level of attitude towards science median of the scale was taken as cut point for labeling, attitude towards science as positive or negative. Independent sample t test was used for comparison on gender basis. Major findings of the study were: Maximum of secondary school students like science to be studied. Girls liked science more than male students. Attitude of male and female with female had more positive attitude towards science. There was a great mean significant difference between career interests in science on gender basis. It shows that female students want more to make career in science. It was recommended that students should be taught by activity-based method and laboratory work in interesting manner to improve the attitude to be more positive.